GOOD FEDERATION, CONFEDERATION, BAD FEDERATION: WHY THE AMERICAN CONTROVERSY ON THE FEDERAL UNION SHOULD BE A LESSON FOR THE EUROPEAN UNION - GHERASIM, Gabriel C. (Studia Universitatis Babeș-Bolyai Philologia, 2017)
Good Federation, Confederation, Bad Federation: Why the American Controversy on the Federal Union Should Be a Lesson for the European Union. The aim of this paper is that of revisiting the competing doctrines of federalism in the United States, as they are exemplarily prescriptive about the means and finality of the correspondent process of European integration. Considering the three main glosses on the federal idea in the United States as the Anti-federalist idea, the Confederative experiment and the Federalist focus on strong and centralized government, the present paper will substantively argue for the (in)consistencies of these models and acknowledge the limits of American federal experiences in the uncertain context of the European controversies on the topic. REZUMAT. Federalismul bun, confederația, federalismul rău: de ce controversele americane privind uniunea federală ar trebui să constituie o lecție pentru Uniunea Europeană. Scopul acestui articol este de a recapitula doctrinele conflictuale ale federalismului american, întrucât ele sunt în mod exemplar prescriptive în privința mijloacelor și scopului procesului integrării europene. Având în vedere cele trei mari accente ale ideii federale în Statele Unite, respectiv, ideea antifederală, modelul experimental confederativ și abordarea federalismului privind ideea unui guvernământ puternic și centralizat, prezentul articol va argumenta pentru (in)consistențele acestor modele și va da seama de limitele experiențelor federale americane în contextul incert al controverselor europene în domeniu. Cuvinte cheie: federalism, confederație, Constituția americană, federaliști, antifederaliști, state, guvernământ centralizat, devoluție.